Effectiveness of Poly Aluminum Chloride Coagulant On The Performance of IPAM Badaksinga, Bandung City - Tati Artiningrum; Mahesa Filiceldi (Green Publisher Indonesia, 2023)
The Badaksinga Drinking Water Processing Installation is an installation owned by Perumda Tirtawening Drinking Water, Bandung City, has 2 of these installations, the first of which is a design from Degremont - France, built around 1954 with a capacity of 1000 liters/second. The second installation is an IWACO-Dutch design with a flow rate of 800 liters/second. The raw water for the two installations comes from the Cisangkuy River and the Cikapundung River. To purify the raw water, PAC (Poly Aluminum Chloride) is used as a coagulant which is a complex inorganic compound with a clear to yellowish color. The coagulant addition process must be carried out efficiently because this coagulation process is a chemical process that requires a large amount of money for the water treatment process apart from chlorination. Excessive addition of coagulant doses will cause the cost of using coagulant chemicals to swell so that it will have an impact on overall operational costs. The purpose of this study was to determine the effectiveness of using PAC in reducing turbidity, in the form of the optimum dose of coagulant, turbidity and pH. The method used is the Jar Test which is a tool to test the ability of coagulants to determine the optimum dose in a water treatment process. From the samples, the raw water turbidity varied from 17.1 to 281 NTU, fluctuating due to geographical location and environmental conditions around each and the degree of acidity or an average pH of 7.13. After the Jar Test was carried out, the optimum dose was produced at a coagulant concentration of 30 mg/l resulting in turbidity in the range of 1.1 to 5.0 NTU and an average turbidity reduction efficiency of 94.5%, the pH of raw water, after coagulation and flocculation with the Jar Test simulation tool, there was a decrease of 4.1% to an average of 6.99. This result is in accordance with Minister of Health Regulation No 492/MENKES/PER/10/2010 April 19 2020, namely turbidity of no more than 5 NTU and a pH of 6.5 – 8.5